Color variation of a damselfish, Stegastes flavilatus (Perciformes: Pomacentridae), from the Pacific coast of Costa Rica and comparison with a sympatric congener - Murase, Atsunobu; Angulo, Arturo [UNESP]; Sahara, Ryosuke; Jiménez, Olger Núñez (My University, 2016)
This note reports four specimens of the damselfish Stegastes flavilatus, captured in the Pacific coast of Costa Rica, with an abnormal coloration pattern. We herein compare morphologically these specimens with normal specimens of S. flavilatus and other sympatric congener.
Keywords: Color information; Distinctive character; Reef fish; Stegastes acapulcoensis; Tropical Eastern Pacific